Evaluation of current bacteriological profile and antibiotic sensitivity pattern in Chronic Suppurative Otitis Media (CSOM) - Draman, Wan Nur Anis Wan (2020)
To determine the current bacteriological profile of CSOM, their antimicrobial sensitivity and resistance pattern towards local antibiotic used and the most sensitive antibiotic against isolated bacteria causing CSOM. This was a cross-sectional study involving a total of 91 ear swabs obtained from patients clinically diagnosed of active CSOM. These swabs were cultured for microbial identification done according to the standard protocol. Microbiological laboratory diagnostic and antibiotic susceptibility testing was performed using Modified Kirby-Bauer’s disc diffusion method. The diameter of inhibitory zone interpreted based on CLSI 2017. Microbial growth was seen in 85 (93.4%) samples while 6 (6.6%) of the samples had no growth. Out of total growth, 63(69.2%) were monomicrobial, 13(14.3%) were polymicrobial and 9 (9.9%) were mixed growth. The most common bacteria isolated was Pseudomonas aeruginosa (32.6%) followed by Staphylococcus aureus(16.9%) and Klebsiellaspp(5.6%). Pseudomonas aeruginosashowed highest sensitivity towards ceftazidime, meropenem and piperacillin-tazobactam. Staphylococcus aureusshowed highest sensitivity to rifampin, cefoxitin and fusidic acid. The commonest microorganism isolated in CSOM was aerobes which were Pseudomonas aeruginosa and Staphylococcus aureus. There is a difference in their antibiotic sensitivity and resistance pattern. This knowledge is important to guide a rational antibiotic use for an effective treatment of CSOM.